Optimization of Non-Hazardous and Toxic Waste (B3) Management from Airside Aircraft Operations: A Case Study of Adi Soemarmo Airport - Desnanda Bintang Berliana; Dwi Candra Yuniar; Anton Abdullah (Utan Kayu Publishing, 2025)
Adi Soemarmo Airport serves domestic and international flights that generate waste from airport operations and aircraft operations. One waste storage site (TPS) is provided. The establishment of the TPS is specifically to manage waste from airport operations, this is based on the Letter of Coordination Agreement (LOCA) which states that the waste from aircraft operations is managed by the ground handling party. However, in its daily activities, there is still scattered and piled up waste in the airport airside area which is dominated by non-hazardous and toxic waste. Therefore, this study aims to find efforts to optimize the management of non-hazardous and toxic waste from aircraft operations at Adi Soemarmo Airport. This research uses descriptive qualitative research methods and data collection techniques using observation for four months, interviews with three informants, and accompanied by documentation. The results of this study obtained four optimal efforts that can be done, namely evaluating the LOCA between ground handling and PT Angkasa Pura I, socializing the importance of airside area cleanliness, making written SOPs, and providing special facilities for aircraft waste. The results are expected to be used by other researchers to optimize the management of waste from aircraft operations in the airport airside area so as to realize an airside area that is free from everything that has the potential to cause events and accidents